AB0723 Subclinical ultrasound synovitis in a particular joint is associated with ultrasound evidence of bone erosions in the same joint, in patients with rheumatoid arthritis in clinical remission. (23rd January 2014) - Vreju, F.; Filippucci, E.; Gutierrez, M.; Di Geso, L.; Ciurea, P.; Salaffi, F.; Grassi, W.
Abstract : Objectives: the aim of the present study was to investigate the relationship between ultrasound (US) findings indicative of joint inflammation and both clinical and US features characterizing synovitis at joint level in patients with rheumatoid arthritis in sustained clinical remission. Methods: 24 consecutive patients with rheumatoid arthritis in clinical remission according to EULAR criteria (DAS28<2.6) underwent clinical and ultrasound (US) assessment. US examination included second to fifth metacarpophalangeal joints of both hands and used a multiplanar scanning technique according to the EULAR guidelines. Results: A total of 192 metacarpophalangeal joints were assessed in 24 rheumatoid arthritis patients in clinical remission, defined by EULAR criteria (DAS28<2, 6). Ultrasound examination found more active joints that clinical evaluation, both by grayscale (GS) and Power Doppler (PD). 105 joints from the total number of 192 had GS changes (54, 68%). By scanning more than one aspect of a joint, we found 56 areas positive for erosions, in both hands, with more than half being hot erosions (53, 57% positive for PD). Both, the median/average Power Doppler score and GS score were higher in the joints with erosions compared to those without erosions (p<0, 01). Conclusions: Joint with bone erosions are more frequently ultrasound inflamed, which explains the fact that treating the rheumatoid arthritis in the window of opportunity, before the radiological changes occur, would offer a higher chance of remission. In the same time suggests that some of the joints need local anti-inflammatory treatment, besides the systemic therapy with DMARDS Disclosure of Interest: None Declared